Effect of genotype and environment on hard wheat water absorption tolerance - Rattin, Gabriela Eyng (Kansas State University, 2011)
Water absorption tolerance is an important parameter in commercial bread production. Hard winter wheat (HWW) flours have shown different water absorption tolerance behaviors in routine wheat quality analysis. Flours with high water absorption tolerance allow broader variation in water addition without affecting optimum dough conditions. Although studies have demonstrated that genotype and environmental factors affect optimum water absorption, mixing time and dough strength, there is no research defining or quantifying water absorption tolerance behavior or explaining reasons and factors affecting such behavior and its correlation with end product quality. Using the mixograph®, this study identified high and low absorption tolerance behaviors in five HRW varieties (Jagger, Jagalene, Fuller, 2137 and Overley) grown in six locations (Finney, Labette, Republic, Thomas, Riley and Sumner Counties) in Kansas, during crop year 2009. Milling, wheat and flour quality tests, Solvent Retention Capacity (SRC), damaged starch, protein composition and identification, flour and starch particle size distribution and bread baking tests were conducted and analyzed. Jagger grown at Finney County possessed the largest water absorption tolerance range while the smallest range was observed for Fuller grown at Riley and Sumner Counties. A positive high correlation was observed between water absorption tolerance and the following parameters: protein content, kernel hardness, extractable polymeric proteins, unextractable polymeric proteins, gliadins and flour particle size (41-300 μm). SDS PAGE and proteomic analyses determined that γ-gliadins were present in a significantly higher concentration in the high tolerance sample suggesting that these proteins play a primary role in water absorption tolerance behavior. The five wheat varieties grown at locations with high and low water absorption tolerance were blended together by location and test baked at three different absorption levels. Loaf volume varied between flours but did not vary between different water levels. It is unclear if this was an effect of the differing protein contents of the blends, water tolerance or both. However, a negative effect on crumb grain characteristics was observed when lower water levels were used.
Keywords: Water absorption tolerance; Hard winter wheat; Environment; Genotype; Mixograph; Food Science (0359)